2023
DOI: 10.3389/fonc.2022.1078916
|View full text |Cite
|
Sign up to set email alerts
|

Mild oxidative stress protects against chemotherapy-induced hair loss

Abstract: Chemotherapy induces hair loss in most cancer patients who undergo treatment, which causes them significant psychosocial trauma. Scalp cooling has demonstrated some efficacy in attenuating chemotherapy-induced alopecia, but response rate varies between patients and chemotherapy class. Here, we showcase in rats a proof-of-concept treatment of using subcutaneous hydrogen peroxide and cumene hydroperoxide injections to provide total protection from hair loss against multiple classes of chemotherapy. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Earlier research demonstrated that oxidative stress triggers the activation of the P53 pathway, inducing cell cycle arrest in the hair follicles and skin. [14] In order to sustain intracellular balance, antioxidants must regulate prooxidant activity, employing 4 lines of defense. [15][16][17] The primary defense against imbalance involves antioxidant enzymes, aimed at preventing free radical formation and neutralizing existing radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research demonstrated that oxidative stress triggers the activation of the P53 pathway, inducing cell cycle arrest in the hair follicles and skin. [14] In order to sustain intracellular balance, antioxidants must regulate prooxidant activity, employing 4 lines of defense. [15][16][17] The primary defense against imbalance involves antioxidant enzymes, aimed at preventing free radical formation and neutralizing existing radicals.…”
Section: Introductionmentioning
confidence: 99%